The feasibility study of using local hematite as weighting material in an oil-based mud system - Ismail, Issham (JSPC & VCC of National Universiti in Malaysia, 1994)
This paper dicusses the prospect of utilising local hematite as weighting material in an oil-based mud system. The discussion was based on laboratory experiments, which were performed at the Faculty of Chemical & Natural Resources Engineering of Universiti Teknologi Malaysia. In this study, the performance of local hematite was evaluated by comparing it to barite, a conventional weighting material used in the oil industry. All the tests were performed according to the API standard procedures. The preliminary results from this study reveal that the local hematite has the potential to be used as weighting material in oil-based drilling fluid.